Wirtschaftszahlen (Stand: 15.08.2025) - Johann Heinrich von Thünen-Institut (German Journal of Agricultural Economics)
Wirtschaftszahlen: This database contains general data on the development of agricultural producer and input prices, the consumer price index and foreign trade in agricultural and food goods on a monthly basis for the previous 24 months. In addition, this database comprises important volume and price developments on national and international markets for selected product groups of agricultural products such as grain, livestock, meat, milk and dairy products as well as vegetables, fruit and sugar. This file is only available in German.